Electronic Load Controller Generator Induksi untuk Pembangkit Listrik Pikohidro: Analisis dan Perancangan Hardware - Krismadinata Krismadinata; Ali Basrah Pulungan (invotek, 2025)
Pico-hydropower plants (PHP) utilize water flow energy with low head to generate small-scale electrical power. In induction generator–based PHP systems, changes and imbalance in three-phase loads can disturb voltage and frequency. This study analyzes and develops the hardware design of an electronic load controller (ELC) based on a three-phase AC-AC converter for an induction-generator-based pico-hydropower system. The design process comprised analysis of the system and generator characteristics, specification of hardware requirements, development of the power and control circuits, and integration of the selected components. The proposed ELC directs surplus active power to a dump load, while independently controlled TRIACs enable per-phase power regulation. The resulting design integrates the excitation capacitor, measurement circuits, gate drivers, an arduino mega controller and the AC-AC power stage. It provides a basis for subsequent prototype validation under balanced, varying, and unbalanced loads. Because experimental performance testing was not conducted, its effects on voltage regulation, frequency stability, harmonics, and long-term reliability remain to be established.